Step
*
2
of Lemma
satisfies-shadow-inequalities
1. n : ℕ
2. ineqs : {L:ℤ List| ||L|| = n ∈ ℤ}  List
3. i : ℕ+n
4. xs : ℤ List
5. (∀as∈ineqs.xs ⋅ as ≥0)
6. ∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)
⊢ (∀as∈shadow-inequalities(i;ineqs).xs\i ⋅ as ≥0)
BY
{ Assert ⌜map(λL.L\i;filter(λL.(L[i] =z 0);ineqs)) ∈ ℤ List List⌝⋅ }
1
.....assertion..... 
1. n : ℕ
2. ineqs : {L:ℤ List| ||L|| = n ∈ ℤ}  List
3. i : ℕ+n
4. xs : ℤ List
5. (∀as∈ineqs.xs ⋅ as ≥0)
6. ∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)
⊢ map(λL.L\i;filter(λL.(L[i] =z 0);ineqs)) ∈ ℤ List List
2
1. n : ℕ
2. ineqs : {L:ℤ List| ||L|| = n ∈ ℤ}  List
3. i : ℕ+n
4. xs : ℤ List
5. (∀as∈ineqs.xs ⋅ as ≥0)
6. ∀L:ℤ List. ((L ∈ ineqs) 
⇒ i < ||L||)
7. map(λL.L\i;filter(λL.(L[i] =z 0);ineqs)) ∈ ℤ List List
⊢ (∀as∈shadow-inequalities(i;ineqs).xs\i ⋅ as ≥0)
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  ineqs  :  \{L:\mBbbZ{}  List|  ||L||  =  n\}    List
3.  i  :  \mBbbN{}\msupplus{}n
4.  xs  :  \mBbbZ{}  List
5.  (\mforall{}as\mmember{}ineqs.xs  \mcdot{}  as  \mgeq{}0)
6.  \mforall{}L:\mBbbZ{}  List.  ((L  \mmember{}  ineqs)  {}\mRightarrow{}  i  <  ||L||)
\mvdash{}  (\mforall{}as\mmember{}shadow-inequalities(i;ineqs).xs\mbackslash{}i  \mcdot{}  as  \mgeq{}0)
By
Latex:
Assert  \mkleeneopen{}map(\mlambda{}L.L\mbackslash{}i;filter(\mlambda{}L.(L[i]  =\msubz{}  0);ineqs))  \mmember{}  \mBbbZ{}  List  List\mkleeneclose{}\mcdot{}
Home
Index